Modelling and simulation study of the influence of size and surface functionality on the stability of PEG-functionalised AgNPs. Issue 2 (22nd January 2023) - Ngake, T.; Gulumian, M.; Cronjé, S.; Harris, R.A.
ABSTRACT: Silver nanoparticles (AgNPs) are useful in various applications due to their unique chemical and physical properties. Therefore, it is important to understand the stability of AgNPs for the development of practical applications. Differently functionalised AgNPs will have different physicochemical properties. This will lead to a variation in the toxicity of these NPs. Different functional groups (FGs) can form coordination bonding or electrostatic interactions with AgNPs. In this study, three different sizes of AgNPs were functionalised by PEG molecules containing five different FGs including methyl, carboxyl, amine, hydroxyl and biotin to investigate the stability of AgNPs in terms of size and FG. The stability was determined by calculating the binding energy of the PEGylated-AgNP system. The results indicate that the stability increases with size, while the influence of the FG was observed to be size-dependent.